2016
DOI: 10.1002/brb3.484
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous dopamine reduces GABA receptor availability in the human brain

Abstract: BackgroundWhile it has recently been shown that dopamine release stimulates conscious self‐monitoring through the generation of gamma oscillations in medial prefrontal/anterior cingulate cortex, and that the GABAergic system is effective in producing such oscillations, interaction of the two transmitter systems has not been demonstrated in humans. We here hypothesize that dopamine challenge stimulates the GABA system directly in the medial prefrontal/anterior cingulate region in the human brain.MethodsPositron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…As reported previously (Lou, Rosenstand et al, ), exogenous dopamine activates GABA neurotransmission in healthy controls. After placebo, highest [ 11 C]Ro15‐4513 BDZ ligand binding was seen in medial prefrontal/anterior cingulate cortex and left and right insula.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…As reported previously (Lou, Rosenstand et al, ), exogenous dopamine activates GABA neurotransmission in healthy controls. After placebo, highest [ 11 C]Ro15‐4513 BDZ ligand binding was seen in medial prefrontal/anterior cingulate cortex and left and right insula.…”
Section: Discussionsupporting
confidence: 82%
“…Hoerbelt, Lindsley, and Fleck () have demonstrated that the dopaminergic system regulates GABA receptors directly in the striatum using the patch‐clamp technique. In our previous report (Lou, Rosenstand et al, ) we showed that dopaminergic activation of GABA release occurs directly throughout the paralimbic cortex, in particular in the medial prefrontal cortex. This binding is compromised in individuals suffering from problem gambling—as shown here.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…With this ligand, we were able to detect changes in dopamineinduced GABA binding under different physiological conditions at well-defined brain sites (Lou et al, 2016). It was found that GABA ligand binding was maximal in the medial anterior paralimbic region (cingulate gyrus), indicating empty GABA binding sites in these locations.…”
Section: Site Of Dopamine-gaba Interactionmentioning
confidence: 99%